Exam 2 - Miller, Kierste Exam 2 Due: Oct 31 2007, 5:00 pm...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Miller, Kierste Exam 2 Due: Oct 31 2007, 5:00 pm Inst: JEGilbert 1 This print-out should have 18 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find a vector function that represents the curve of intersection of the cone z = p x 2 + y 2 and the plane z- y = 13. 1. r ( t ) = t i + t 2- 169 26 j + t 2 + 169 26 k correct 2. r ( t ) = p 13(2 t + 13) i + ( t- 13) j + t k 3. r ( t ) = t 2- 169 26 i + t j + t 2 + 169 26 k 4. r ( t ) = t 2- 169 26 i + t j + t 2 + 13 26 k 5. r ( t ) = p 13(2 t- 13) i + t j + ( t + 13) k Explanation: The vector function r ( t ) = x ( t ) i + y ( t ) j + z ( t ) k intersects the cone z = p x 2 + y 2 and the plane z- y = 13 when z ( t ) = q x ( t ) 2 + y ( t ) 2 , z ( t )- y ( t ) = 13 . Now this last condition already eliminates two of the answer choices, leaving only r ( t ) = t i + t 2- 169 26 j + t 2 + 169 26 k , r ( t ) = p 13(2 t + 13) i + ( t- 13) j + t k , and r ( t ) = p 13(2 t- 13) i + t j + ( t + 13) k . But only the first of these equations defines a curve lying on the cone z = p x 2 + y 2 . Consequently, only r ( t ) = t i + t 2- 169 26 j + t 2 + 169 26 k lies on both the cone and the plane. keywords: 002 (part 1 of 1) 10 points Determine f xy when f ( x, y ) = 2 xy ln( xy )- 3 xy . 1. f xy = 2(ln( xy- xy ) + 1 2. f xy = 4(ln( xy ) + xy )- 1 3. f xy = 4(ln( xy )- xy ) + 1 4. f xy = 2ln( xy ) + 1 correct 5. f xy = 4ln( xy )- 1 6. f xy = 2ln( xy )- 1 Explanation: Since ln( xy ) = ln x + ln y , we see that f ( x, y ) = 2 xy (ln x + ln y )- 3 xy . But then, f x = 2 y (ln x + ln y ) + 2 xy x- 3 y = 2 y (ln x + ln y )- y , in which case f xy = 2(ln x + ln y ) + 2 y y- 1 = 2(ln x + ln y ) + 1 , Miller, Kierste Exam 2 Due: Oct 31 2007, 5:00 pm Inst: JEGilbert 2 after differentiating with respect to y . Conse- quently, f xy = 2ln( xy ) + 1 . keywords: partial derivative, mixed partial derivative, log function, 003 (part 1 of 1) 10 points Find the arc length of the curve r ( t ) = (1- 2 t ) i + ln(2 t ) j + (3- t 2 ) k between r (1) and r (3). 1. arc length = 8 + ln3 correct 2. arc length = 3 + ln6 3. arc length = 9 + 2ln3 4. arc length = 8- 2ln3 5. arc length = 6- ln3 6. arc length = 8- ln3 Explanation: The length of a curve r ( t ) between r ( t ) and r ( t 1 ) is given by the integral L = Z t 1 t | r ( t ) | dt . Now when r ( t ) = (1- 2 t ) i + ln(2 t ) j + (3- t 2 ) k we see that r ( t ) =- 2 i + 1 t j + 2 t k ....
View Full Document

Page1 / 9

Exam 2 - Miller, Kierste Exam 2 Due: Oct 31 2007, 5:00 pm...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online